## Answer :

### Step-by-Step Solution:

#### Step 1: Reflection across Line 1, [tex]\(x = -2\)[/tex]

When reflecting a point [tex]\((x, y)\)[/tex] across a vertical line [tex]\(x = c\)[/tex], the formula to find the reflected point is [tex]\((2c - x, y)\)[/tex]. Here, Line 1 is [tex]\(x = -2\)[/tex]. Our original point is [tex]\((0, 0)\)[/tex].

1. Apply the reflection formula:

[tex]\[ x' = 2c - x = 2(-2) - 0 = -4 \][/tex]

[tex]\[ y' = y = 0 \][/tex]

So, the coordinates of the point after the first reflection are:

[tex]\[ (-4, 0) \][/tex]

#### Intermediate Point:

The coordinate after the first reflection is [tex]\((-4,0)\)[/tex].

#### Step 2: Reflection across Line 2 (the [tex]\(y\)[/tex]-axis)

When reflecting a point [tex]\((x, y)\)[/tex] across the [tex]\(y\)[/tex]-axis, the formula to find the reflected point is [tex]\((-x, y)\)[/tex]. Here, the intermediate point is [tex]\((-4, 0)\)[/tex].

1. Apply the reflection formula:

[tex]\[ x'' = -x = -(-4) = 4 \][/tex]

[tex]\[ y'' = y = 0 \][/tex]

So, the coordinates of the point after the second reflection are:

[tex]\[ (4, 0) \][/tex]

### Conclusion:

After performing these two reflections sequentially, the final image of the point [tex]\((0, 0)\)[/tex] is [tex]\((4, 0)\)[/tex].

The correct answer is:

[tex]\[ \boxed{(4, 0)} \][/tex]